Peningkatan Kapasitas UMKM Melalui Pelatihan Negosiasi Dan Strategi Penjualan Di Dusun Karang Nongko Tajinan, Kabupaten Malang - Yoan Santosa Putra; Dimas Emha Amir Fikri Anas; Kowiyanto (Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in promoting local economic growth, particularly in rural areas. However, MSME actors in Karang Nongko Hamlet, Tajinan District, Malang Regency, still face various limitations, especially in negotiation skills and sales strategies. This community service activity aims to enhance the understanding, skills, and self-confidence of MSME actors through practical and contextual training in negotiation and sales strategies. The methods employed include preliminary observation, interviews, face-to-face training based on andragogical principles, simulations, role-playing, and interactive discussions. The results of the program indicate that the training successfully improved participants’ conceptual understanding of negotiation and sales processes, strengthened persuasive communication skills, and increased self-confidence in dealing with customers and business partners. Participant responses and engagement were very positive, as reflected by high attendance, active involvement during the training sessions, and a strong commitment to applying the acquired knowledge in their business practices. This activity contributes positively to strengthening the capacity and competitiveness of local MSMEs and demonstrates that needs-based training is an effective strategy for sustainable MSME empowerment.